Does political risk matter for economic and financial risks in Venezuela? - Dervis Kirikkaleli (Journal of Economic Structures, 2020)
In this paper, the time-frequency dependency of political risk as well as economic and financial risks is explored in Venezuela using quarterly data from 1984Q1 to 2018Q4. The present study uses the wavelet coherence technique, which allows the investigation of both the long and short-term causal relationships between political risk and economic and financial risks in Venezuela. The findings of this study indicate that: (i) significant vulnerabilities in political risk, economic risk, and financial risk are observed at different time periods and different frequency levels; (ii) political risk has a strong power for explaining economic risk from 1995 to 2005 in the long run, while between 1984 and 2010, economic risk and political risk are positively correlated at different frequency levels; (iii) in the long run, changes in political risk significantly lead to changes in financial risk in Venezuela.
Keywords: R11; E5; G0; P16; C60; 330; Political risk; Venezuela; Financial risk; Economic risk; Wavelet coherence